1974
DOI: 10.1051/rnd:19740404
|View full text |Cite
|
Sign up to set email alerts
|

l'INSÉMINATION Artificielle De La Truite (Salmo Gairdneri Richardson). Iii. — Définition De La Nature Et De La Molarité Du Tampon a Employer Avec Les Dilueurs d'INSÉMINATION Et De Conservation

Abstract: Des expériences ont été conduites dans le but de définir la nature et la molarité du tampon à utiliser avec les deux dilueurs d'insémination et de conservation définis précédemment. Les effets des différents tampons ont été testés d'une part sur la stabilité du pH du dilueur après introduction de quantités croissantes de NaOH et HCI, de liquide coelomique et d'ovules et d'autre part sur le pourcentage de fécondation établi sur de petits lots de 200 ovules. Les conclusions sont les suivantes : 1° Le dilueur d'i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

1975
1975
2008
2008

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 0 publications
0
1
0
1
Order By: Relevance
“…Kusa (1950) reported that Oncorhynchus keta spermatozoa lost their fertilizing ability in Ringer’s solution after 90 min; however, the latter can be regained after 24 h. After dilution of Salmo trutta sperm in Ringer’s solution, Ginsburg (1972) noted a loss of fertility 20 min later, but a complete recovery was observed after 90 and 120 min. The same pattern was also found for spermatozoa treated with ovarian fluid although sperm ability to fertilize was at a lower level (Billard et al., 1974). When inseminating eggs at consecutive intervals, dilution of Oncorhynchus keta milt in Ringer’s medium (followed by a second dilution in the same medium) resulted in a gradual decrease in fertilizing ability down to zero at 120 min (Yamamoto, 1961).…”
Section: Introductionmentioning
confidence: 99%
“…Kusa (1950) reported that Oncorhynchus keta spermatozoa lost their fertilizing ability in Ringer’s solution after 90 min; however, the latter can be regained after 24 h. After dilution of Salmo trutta sperm in Ringer’s solution, Ginsburg (1972) noted a loss of fertility 20 min later, but a complete recovery was observed after 90 and 120 min. The same pattern was also found for spermatozoa treated with ovarian fluid although sperm ability to fertilize was at a lower level (Billard et al., 1974). When inseminating eggs at consecutive intervals, dilution of Oncorhynchus keta milt in Ringer’s medium (followed by a second dilution in the same medium) resulted in a gradual decrease in fertilizing ability down to zero at 120 min (Yamamoto, 1961).…”
Section: Introductionmentioning
confidence: 99%
“…Le matériel animal et les conditions expérimentales ont été définies dans les notes précédentes BILLARD, JALABERT, BRETON, 1974). Les expériences spécifiquement conduites dans cette étude sont les suivantes :…”
Section: Materiel Et Methodesunclassified